PARADIGMA IJTIHAD FIQH MINORITAS DI INDONESIA - Dahlan, Moh (Analisis: Jurnal Studi Keislaman, 2012)
Indonesia is a famously religious nation that has a high-level of plurality in many aspects of race/ethnicity, religion, belief, language, customs, political thoughts, economic, cultural and ideological. All these could potentially contribute conflict and tension between different groups if the attitude of extreme and formalistic  logic of fiqh flourished. This paper tryies to emphasize the importance of fiqh aqalliyah in the era of pluralism to organize the life among different religious believers in which religious conflict has often been the case due to double standards and the Islamic militant movement. By means of Kuhn’s shifting paradigm approach, this paper reveals that Muslims need to formulate a shifting paradigm of ijtihad, namely from fiqh aglabiyah   (majority fiqh) to fiqh aqalliyah (minority fiqh), where Muslims can protect non- Muslim minorities and also capable of providing the space for life of Muslims  in the non-Muslim  majority.  Thus, this paper develops  the nature of  paradigm of the fiqh aqalliyah of M. Amin Abdullah, who is only focused on the aspect of giving space to Muslims living in non- Muslim territory. In his presentation, the author emphasizes the need for re-reading  (re-interpret)   the old discourse  of fiqh and submit a new one drafted on the reading of religious texts based on universal religious values such as the conception of  qat}‘i>-z}anni> as proposed by Masdar F. Mas‘udi.